A large exposure to brucella melitensis in a diagnostic laboratory - Sam, I.C.; Karunakaran, R.; Kamarulzaman, A.; Ponnampalavanar, S.; Omar, S.F.S.; Ng, K.P.; Yusof, M.Y.M.; Hooi, P.S.; Jafar, F.L.; AbuBakar, Sazaly (2012)
Background: Brucella species are easily transmitted by aerosols and can be acquired in the laboratory. Aim: To report the management of a large exposure to Brucella melitensis that occurred over six days in a hospital diagnostic laboratory. Methods: Fifty-one exposed staff were managed according to Centers for Disease Control and Prevention guidelines. A further 96 non-exposed laboratory staff were tested for seroprevalence. Testing was carried out using the Brucella sp. serum agglutination test. Findings: Twenty-seven people had high-risk exposure and 24 had low-risk exposure. High-risk staff were offered post-exposure prophylaxis. Twelve (44.4) agreed to this, of whom eight (66.7) completed the course. Overall compliance with serological follow-up at baseline, 2, 4, 6 weeks and 8 months was 45.9. Despite this poor compliance there were no clinical brucellosis cases and no seroconversion in the 47.1 of staff tested at 8 months. Brucella sp. seroprevalence among all staff tested was 3/147 (2.0). Conclusion: Lack of experience with Brucella spp. and lack of policies for handling potentially hazardous organisms contributed to this prolonged exposure. As compliance with current recommendations may be poor, the optimum frequency of serological follow-up and target groups for prophylaxis should be reassessed. Laboratories in low- or non-endemic areas must prepare for potential isolation of Brucella spp. The impact of human brucellosis in Malaysia requires further study. (C) 2011 The Healthcare Infection Society. Published by Elsevier Ltd. All rights reserved.